1995
DOI: 10.1074/jbc.270.43.25645
|View full text |Cite
|
Sign up to set email alerts
|

Amphibacillus xylanus NADH Oxidase and Salmonella typhimurium Alkyl-hydroperoxide Reductase Flavoprotein Components Show Extremely High Scavenging Activity for Both Alkyl Hydroperoxide and Hydrogen Peroxide in the Presence of S. typhimurium Alkyl-hydroperoxide Reductase 22-kDa Protein Component

Abstract: The flavoprotein NADH oxidase from Amphibacillus xylanus consumes oxygen to produce hydrogen peroxide. The amino acid sequence of this flavoprotein shows 51.2% identity to the F-52a component, denoted AhpF, of the alkyl-hydroperoxide reductase from Salmonella typhimurium. AhpF also catalyzes NADH-dependent hydrogen peroxide formation under aerobic conditions, albeit at a somewhat slower rate than the Amphibacillus protein. In the presence of the 22-kDa colorless component (AhpC) of the Salmonella alkyl-hydrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 34 publications
2
106
2
2
Order By: Relevance
“…Substrate inactivation was also shown to occur in the peroxiredoxins (Prxs) from Kinetoplastida, including Leishmania major, L. donovani and Trypanosoma brucei, but not in Crithidia fasciculate (Nogoceke et al, 1997;Castro et al, 2002;Flohe et al, 2002;Budde et al, 2003). In contrast, the homologous bacterial peroxiredoxin AhpC efficiently detoxifies mM levels of hydrogen peroxide and cumene peroxide without any indication of peroxide-dependent inactivation (Niimura et al, 1995;Poole, 1996). Furthermore, in vivo peroxide stress studies in Salmonella typhimurium showed no indication of post-translational modification in AhpC (Christman et al, 1985;Morgan et al, 1986).…”
Section: The Hyperoxidation Of Peroxiredoxinsmentioning
confidence: 99%
“…Substrate inactivation was also shown to occur in the peroxiredoxins (Prxs) from Kinetoplastida, including Leishmania major, L. donovani and Trypanosoma brucei, but not in Crithidia fasciculate (Nogoceke et al, 1997;Castro et al, 2002;Flohe et al, 2002;Budde et al, 2003). In contrast, the homologous bacterial peroxiredoxin AhpC efficiently detoxifies mM levels of hydrogen peroxide and cumene peroxide without any indication of peroxide-dependent inactivation (Niimura et al, 1995;Poole, 1996). Furthermore, in vivo peroxide stress studies in Salmonella typhimurium showed no indication of post-translational modification in AhpC (Christman et al, 1985;Morgan et al, 1986).…”
Section: The Hyperoxidation Of Peroxiredoxinsmentioning
confidence: 99%
“…Interestingly, the two enzymes have different reactivities to oxygen (Niimura et al, 1995). Nox from A. xylanus is more reactive to oxygen than AhpF from S. typhimurium is (Niimura et al, 1995). Therefore, it is thought that the Nox-Prx system is involved not only in the removal of peroxides but also in oxygen metabolism in the aerobic metabolic pathway of A. xylanus (Niimura et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although the physiological function of the NADH oxidase was first thought to be the in-vivo regeneration of NAD in the aerobic metabolism of the bacterium, the enzyme was shown to catalyse the reduction of oxygen by NADH to form hydrogen peroxide (Niimura et al, 1993). Also, the NADH oxidase that acts together with an alkyl hydroperoxide reductase C (AhpC) was found to catalyse the NADH-dependent reduction of both hydrogen peroxide and alkyl hydroperoxides (Niimura et al, 1995). A. xylanus NADH oxidase has 51.2 % amino acid sequence identity with alkyl hydroperoxide reductase F (AhpF) obtained from Salmonella typhimurium (Jacobson et al, 1989;Niimura et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence for this hypothesis is the genome sequence conservation between M. tuberculosis and M. bovis. In addition, a recent study suggested that molecules such as mycothiol may serve as partner molecules in the enzymatic cycle of the mycobacterial alkyl hydroperoxide reductase (AhpC) (27), an enzyme that has been shown to detoxify organic peroxides (24) and possibly H 2 O 2 (28). This enzyme has been implicated in the survival of INH resistant M. tuberculosis, as point mutations in the AhpC gene was associated with drug resistance (29) and its expression was shown to be up-regulated in M. tuberculosis drug resistant phenotypes (30).…”
Section: Discussionmentioning
confidence: 99%